Pseudomonas Aeruginosa Sebagai Indikator Kontaminasi Produk Kosmetika : Tinjauan Literatur - Nafisa Nurfatia Hidayat; Patihul Husni (Vitalitas Medis : Jurnal Kesehatan dan Kedokteran, 2026)
Pseudomonas aeruginosa is a Gram-negative bacterium commonly found in the environment and serves as an important indicator of microbiological contamination in cosmetic products. Its ability to survive in low nutrient conditions and its resistance to various preservatives make it a microorganism frequently found in water-based products. Contamination can occur during production, storage, and use, and has the potential to cause irritation or infection, especially in individuals with low immunity. This literature review was compiled based on data searches on PubMed, Elsevier, Google Scholar, and Scopus with inclusion criteria of original studies from 2015 to 2025 that reported the detection of P. aeruginosa in cosmetic products. The results of the review show that P. aeruginosa is not only found in new products but also in used products, mainly due to unhygienic usage practices. Although some products are declared free from contamination, monitoring of the production process and consumer education on how to use and store cosmetics are still necessary. Thus, the detection and control of P. aeruginosa are important aspects in ensuring the safety of cosmetic products on the market.